Pentingnya Peran Orang Tua dalam Meningkatkan Prestasi Belajar Siswa - Arwen, Desri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
ABSTRACT The purpose of this study was to determine the role of parents in guiding or fostering students, to find out what factors support and hinder the role of parents in improving student achievement, and to determine the role of parents in improving student achievement. This type of research is a field research with a qualitative approach, the data obtained through the methods of observation, documentation, and interviews. The results showed that the role of parents in improving student achievement in the family has been going quite well. The role of parents of students, among others; 1) Parents have created a comfortable and peaceful atmosphere in the home environment, creating good communication between parents and children; 2) Parents of students can condition learning activities and understand students' circumstances. Problems faced by parents at home in improving learning achievement, including; Limited facilities, low interest in children's learning. Relationships and the surrounding environment. Parents try to improve student achievement by providing direction, supervision, and coaching to improve children's achievement; 2) Provide facilities to improve children's achievement; 3) Parents involve their children in activities related to their children's learning, such as tutoring or tutoring; 4) Controlling children studying at home and familiarizing children with discipline with time in doing all activities. In conclusion, the role of parents in improving the learning achievement of grade 3 SD Muhammadiyah Tangerang is very good, covering several aspects, both the role and educational and social background of parents. The role and attention of parents is one of the important factors that can affect children's learning achievement. Keywords: Student Achievement, Role of Parents.